PENGARUH PEMBERIAN INSENTIF PAJAK PPNBM KENDARAAN BERMOTOR DI TENGAH PANDEMI - Zulkarnain, Nizar; Hambali, Ahmad; Candra, Hendra (JURNAL LENTERA AKUNTANSI, 2024)
The COVID-19 pandemic has had a negative influence on economic growth in Indonesia, to overcome this, one of the efforts of the Indonesian government is by providing incentives in the form of reducing taxation, in this case Luxury Goods Sales Tax (PPnBM) on the sale of motor vehicles. This study aims to measure the effectiveness of the policy by comparing car sales data in the period before and after the Covid-19 pandemic. The method used is quantitative descriptive with snowball sampling techniques with the population being all automotive companies in Indonesia, then the data is tested using SPSS tools with data normality test techniques to t-test tests. The results of this study show that the Indonesian government's policy by providing PPnBM incentives to motor vehicles has proven to have a significant positive effect on the sales of motor vehicles (cars) in Indonesia, both in the categories that get incentives and those that do not get incentives are also encouraged in terms of sales. Key words: Tax Incentive; Tax Policy; Luxury Sales Tax